Hospitals as a Service Product an Analysis of the Dimensions of Quality, Characteristics, and Contemporary Marketing Strategies - Dedeh Nurdalillah; Daffa Muhammad Ivandharu; Firman Firdaus; Al Bait Fiqri; Abdillah Al; A. Rohendi (Indonesian Journal Publisher, 2026)
The transformation of hospitals from purely social institutions into socio-economic entities has increased the need for adaptive management and sustainable marketing strategies. Although numerous studies have examined healthcare service quality and hospital marketing, these topics are generally discussed separately, resulting in limited conceptual integration between the unique characteristics of healthcare services, service quality dimensions, and ethical marketing strategies. This study aims to analyze hospitals within the service industry framework, synthesize the dimensions of healthcare service quality from the patient's perspective, and formulate a conceptual framework for contemporary hospital marketing that aligns with professional ethics. This study employed a narrative literature review by systematically searching scientific publications indexed in Google Scholar, Scopus, and ScienceDirect using the keywords hospital service marketing, healthcare service quality, SERVQUAL, relationship marketing, and hospital marketing strategy. The literature selection focused primarily on publications from 2015–2025, while several seminal works were retained to establish the theoretical foundation. The collected literature was analyzed using content analysis to identify recurring themes, compare findings, and synthesize conceptual relationships. The review indicates that patients tend to evaluate hospital quality primarily through functional quality, particularly empathy and responsiveness, rather than technical quality because of information asymmetry in healthcare services. Furthermore, recent literature demonstrates a shift from transactional marketing toward value-based marketing, emphasizing patient experience, digital health services, and Patient Relationship Management (PRM). The conceptual contribution of this study lies in integrating healthcare service characteristics, service quality dimensions, and ethical marketing strategies into a comprehensive analytical framework. Practically, the findings provide guidance for hospital managers in strengthening patient experience, implementing service digitalization, and developing sustainable marketing strategies without compromising clinical quality and professional ethics.